PATIENT RIGHTS OF SOCIAL BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) PARTICIPANTS REGARDING THE FULFILLMENT OF MEDICATION NEEDS BY HOSPITALS - Situmeang, Sahat Maruli Tua; Mile, Tiara (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The government provides health services through the BPJS social security program. However, complaints often arise regarding the lack of availability of medicines for BPJS patients in hospitals so that they require out-of-pocket costs. This research aims to determine the rights to provide health services and treatment for BPJS patients, as well as legal protection against fraud in hospitals. Using normative juridical methodology, this research uses descriptive analysis to describe secondary and primary facts. Data sourced from regulations, publications and websites, through literature studies. The research results show that drug services to BPJS patients are influenced by state budget limitations in administering health insurance. Based on this, it is important to confirm the availability of drugs between pharmacists and prescribing doctors and establish protocols for providing drugs, and offer profitable alternatives for patients in an effort to improve health services.